The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.1186/s12884-017-1351-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of pregnancy-relevant infections in a rural setting of Ghana

Abstract: BackgroundAlthough infectious diseases still account for a high burden of morbidity and mortality in sub-Saharan Africa, simultaneous investigations on multiple infections affecting maternal and child health are missing.MethodsWe conducted a cross-sectional, single-centre pilot study in a rural area of Ghana to assess the infectiological profile during pregnancy. Screening of 180 expectant mothers was done by vaginal swabs and serology to detect the most common pregnancy-relevant infections. They were also int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 26 publications
(27 reference statements)
2
33
2
Order By: Relevance
“…We accessed 11 full articles reporting the prevalence of CMV in pregnancy in Africa. Of the 11 studies, two were conducted in North Africa (both in Egypt [29,30]), four in West Africa (one in each of Gambia [31] and Ghana [32], two in Nigeria [33,34]), four in East Africa (one in each of the following countries; Ethiopia [35], Kenya [36], Sudan [37] and Tanzania [38]); and one in Southern Africa (Malawi) [39].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We accessed 11 full articles reporting the prevalence of CMV in pregnancy in Africa. Of the 11 studies, two were conducted in North Africa (both in Egypt [29,30]), four in West Africa (one in each of Gambia [31] and Ghana [32], two in Nigeria [33,34]), four in East Africa (one in each of the following countries; Ethiopia [35], Kenya [36], Sudan [37] and Tanzania [38]); and one in Southern Africa (Malawi) [39].…”
Section: Resultsmentioning
confidence: 99%
“…Exposure to CMV among African pregnant women in the reviewed studies was very high, but appears to vary across the continent. The prevalence of active infection, denoted by presence of IgM antibodies (0-15.5%), was much lower than that of IgG antibodies (60-100%) [29][30][31][32][33][34][35][36][37][38][39]. However, the seroprevalence of both CMV IgG and IgM antibodies did not show any geographic trends across the African continent.…”
Section: Seroprevalence Of CMVmentioning
confidence: 99%
See 1 more Smart Citation
“…The prevalence found in this study is lower than prevalence from in rural settings. A cross-sectional survey among pregnant women in rural Ghana found a seroprevalence of 16.7% [26]. This indicates that HBV prevalence is higher in rural Ghana [23].The differences in findings might be due to differences in awareness and access to vaccination centers.…”
Section: Discussionmentioning
confidence: 99%
“…A South African study exploring prevalence of B19V infection among pregnant women found 20 asymptomatic neonates born to IgM positive mothers, although no samples from newborns were obtained[ 66 ]. Different African studies on maternal B19 V seroprevalence found IgG AB between 24.9 and 80% and IgM between 3 and 19%[ 66 – 70 ]. Unfortunately, maternal seroprevalence was not performed in this study and further research should be done in order to know the real burden of congenital B19V.…”
Section: Discussionmentioning
confidence: 99%